Gender norms in agri-food systems: Economic resilience - Farnworth, Catherine Rozel; Morahan, Rebecca; Rietveld, Anne (2024)
Annotated bibliography: This annotated bibliography (AB) provides a research overview on the basis of 77 articles. The annotated bibliography was produced to support an evidence synthesis on gender norms in agri-food systems (Rietveld et al., 20231). The aim of the evidence synthesis was to describe how gender norms facilitate, or hamper, women’s abilities to achieve economic resilience in the face of climate change challenges. For each article the title and citation are listed and a description is provided. The description covers the research topic, the methodology, the research findings and conclusions of the article. Sometimes the reviewer has added additional comments.